Tailoring tokamak error fields to control plasma instabilities and transport - Yang, SeongMoo; Park, Jong-Kyu; Jeon, YoungMu; Logan, Nikolas C.; Lee, Jaehyun; Hu, Qiming; Lee, JongHa; Kim, SangKyeun; Kim, Jaewook; Lee, Hyungho; Na, Yong-Su; Hahm, Taik Soo; et al. (Nature communications, 2024)
A tokamak relies on the axisymmetric magnetic fields to confine fusion plasmas and aims to deliver sustainable and clean energy. However, misalignments arise inevitably in the tokamak construction, leading to small asymmetries in the magnetic field known as error fields (EFs). The EFs have been a major concern in the tokamak approaches because small EFs, even less than 0.1%, can drive a plasma disruption. Meanwhile, the EFs in the tokamak can be favorably used for controlling plasma instabilities, such as edge-localized modes (ELMs). Here we show an optimization that tailors the EFs to maintain an edge 3D response for ELM control with a minimized core 3D response to avoid plasma disruption and unnecessary confinement degradation. We design and demonstrate such an edge-localized 3D response in the KSTAR facility, benefiting from its unique flexibility to change many degrees of freedom in the 3D coil space for the various fusion plasma regimes. This favorable control of the tokamak EF represents a notable advance for designing intrinsically 3D tokamaks to optimize stability and confinement for next-step fusion reactors. Error fields in tokamak appear due to the imperfections and misalignment of the coils generating magnetic field. Here the authors demonstrate use of error field correction to control the plasma transport and instabilities in a tokamak - KSTAR.